How regulation might fail to reduce energy consumption while still stimulating total factor productivity growth - Sangeeta Bansal; Massimo Filippini; Suchita Srinivasan (ETH Zurich, CER-ETH - Center of Economic Research, 2023)
This paper evaluates the impact of a policy that was implemented to reduce the energy intensity of firms in some manufacturing sectors in India, on the total factor productivity (TFP) growth of firms and on its components, scale efficiency and technical change. Using plant-level panel data on the cement industry from 2007-2015 and a difference-in-difference methodology, we find that treated plants had higher rates of TFP growth, compared to control plants. This is largely driven by the fact that they expanded their production compared to control plants, even though they experienced lower rates of technical change compared to control plants. To explain this finding, we verify that treated plants attempted to meet the energy-intensity mandate not by reducing their energy consumption, but instead by increasing their output. Our results suggest that energy intensity regulations may not reduce energy consumption, because firms may find other ways to fulfil targets. The policy implications of this study are related to the design of energy-efficiency regulations, particularly in developing countries where firms in some industries may find it difficult to reduce their energy consumption through investment in new energy-efficient technologies or processes.
Keywords: D1; D8; Q4; Q5; 330; Total factor productivity; Climate change mitigation; Environmental Regulation; Cement Industry; Energy Intensity; India